A formação graduada de terapeutas ocupacionais para o cuidado na atenção primária à saúde no estado de São Paulo - Silva, Rodrigo Alves dos Santos (2016)
It is essential the debate between the formation of the occupational therapist and the Primary Health Care (PHC), both around theoretical and methodological frameworks, such as the pursuit of specific tasks and actions of occupational therapy, since the scientific contributions in this field have little detail for training and professional practice. In this sense, the objective of this study was to describe and analyze the graduate training of occupational therapists to care PHC in higher education institutions in the state of São Paulo. The research has a qualitative approach, exploratory-descriptive and document type. Participated in this investigation, 8 coordinators, 17 teachers and 69 students of 9 occupational therapy courses in the state of São Paulo. Data were built during the interviews, conversation circles and study of institutional documents. Therefore, we used the interview scripts, talk wheel and document analysis. The data were analyzed through thematic categorization. With regard to data obtained from the documents and coordinators, curriculum components were identified, the heterogeneity of curricular designs, the time that PHC is addressed in the training and the number of teachers involved in the teaching of PHC. The data built with the teachers corresponded to five themes: I - vocational training and academic trajectory of occupational therapists teachers in PHC; II - training activities in the fields of education, research and extension, teaching methodologies and essential theoretical content training for PHC; III - Monitoring of students in practical training services and their management mode; IV - care prospects in PHC and care of occupational therapists in PHC: V - contributions to training; the support offered; the powers, the challenges and the changes necessary for focused training for PHC. The construction of the data with the students resulted in four thematic categories: I - knowledge of PHC; II - curricular components and essential content training for care in PHC; III - students concepts about the care of occupational therapists in PHC; IV - Training for PHC, challenges and necessary changes. Through the analysis of these data, it was found that the occupational therapy courses there are theoretical and practical curriculum components of PHC related understanding design on daily life, the territory, intersectoral action and the different individual care strategies and collective to facilitate access to rights through social policies and health care and, thus, support the construction of paths of participation of people in different walks of life. Thus, the construction process of fieldwork and reflections brought about by the study allowed us to analyze the formation processes of occupational therapy have promoted at least a critical professional with specific knowledge, available to be in the PHC and perform a specific job and staff in order to contribute to the development of skilled care to the population.